Mechanical response of multi-layer bacterial cellulose nanopaper reinforced polylactide laminated composites - Hervy,M; Blaker,JJ; Braz,AL; Lee,KY (Composites Part A: Applied Science and Manufacturing, 2018)
In this study, we investigated the mechanical response of polylactide (PLLA) reinforced with multiple layers of BC nanopaper. Laminated composites consisting of 1, 3, 6 and 12 sheet(s) of BC nanopaper were produced. It was observed that increasing the number of BC nanopaper led to an increase in the porosity of the resulting BC nanopaper-reinforced PLLA laminated composites. The tensile moduli of the laminated composites were found to be ∼12.5 – 13.5 GPa, insensitive to the number of sheets of BC nanopaper in the composites. However, the tensile strength of the laminated composites decreased by 21% (from 121 MPa to 95 MPa) when the number of reinforcing BC nanopaper sheets increased from 1 to 12 sheets. This was attributed to the presence and severity of the scale-induced defects increased with increasing BC nanopaper sheets in the PLLA laminated composites.